RADI-36. FRAME-BASED VERSUS FRAMELESS GAMMA KNIFE RADIOSURGERY FOR BRAIN METASTASES. (12th August 2019) - Patel, Ankur; Plitt, Aaron; Mendel, Jameson; Nedzi, Lucien; Timmerman, Robert; Dan, Tu; Barnett, Samuel; Mickey, Bruce; Wardak, Zabi; Patel, Toral
Abstract: INTRODUCTION: Brain metastases occur in 10 to 40% of cancer patients. In an effort to avoid the neurocognitive toxicities of whole brain radiation therapy, stereotactic radiosurgery (SRS) has become the preferred treatment option for most brain metastases. Many cancer patients will require several rounds of SRS during the course of their disease. Frame-based radiosurgery causes physical discomfort with each treatment session. We present our experience with frameless Gamma Knife radiosurgery (GKRS) and compare the clinical outcomes to frame-based treatments in the same patient cohort. METHODS: We evaluated all patients with brain metastases who underwent both frame-based and frameless SRS, using the Gamma Knife ICON, between January 2017 and November 2018. 11 patients with 110 unique lesions were included in this analysis. Clinical outcomes, including local control, were compared between the two treatment modalities. RESULTS: Mean patient age was 60.0 (range: 41 – 76) years. Median follow-up was 7.9 (range: 0 – 22.1) months. Median number of metastases treated was 4 (range: 1 – 9) per frame-based treatment and 3 (range: 1 – 10) per frameless treatment. Median number of frame-based and frameless procedures, per patient, was 1 (range: 1 – 3) and 1 (range: 1 – 2), respectively. Median tumor volume was 0.06 (range: 0.01 – 11.49) cm 3 in the frame-based treatments and 0.14 (range: 0.01 – 4.22) cm 3 in the frameless treatments. Median margin dose was 18 Gy for both the frame-based and frameless treatments. Local control was 86.5 and 91.5% at 6 and 9 months post-treatment, respectively in the frame-based treatments and 82.8 and 87.5% at 6 and 9 months post-treatment, respectively in the frameless treatments. CONCLUSIONS: Frameless GKRS results in similar rates of local control compared to frame-based GKRS. This treatment option should be considered in patients undergoing GKRS, as it balances clinical outcomes with patient comfort.